Superintendents’ Recommendations for a New Federal Framework for Educational Accountability - Dance, S. Dallas (Education Policy Analysis Archives, 2015)
The members of the Large Countywide and Suburban District Consortium—a group of large, highly diverse, and successful districts across the country—have made great strides in achieving college and career readiness for all students. While they are succeeding, the consortium proposes that more could be done to accomplish their objectives through collaboration with Congress to establish federal policy and laws aligned with practices that foster college and career ready outcomes at scale. This article, introduced by Baltimore County Public Schools Superintendent S. Dallas Dance, proposes the critical principles that should undergird a new federal approach to state and district accountability.